Bitter taste receptor-guided delivery of limonin: Bridging taste masking and gut health - Wei-yun Zhang; Jin-song Liao; Jun-ru Qi (Trends in Food Science & Technology, 2026)

From efficient nitrite accumulation to complete collapse: how a microbial community and its antibiotic resistance genes in a nitrification system respond to long-term exposure to ciprofloxacin and copper - Xiao-Yan Fan; Meng-Hao Hao; Jun-Ru Zhao; Xing Li; Shen-Bin Cao; Jia-Wei Ren; Ding-Chang Li (Journal of Water Process Engineering, 2026)

Optimized green extraction of flavonoids from Lycium barbarum leaves using betaine-ethylene glycol NADES: Mechanisms, identification, and bioactivity - Ya-Jie Yuan; Zhen Liu; Yu-Ru Wang; Xin-Yue Zhang; Qian Ma; Cen Xiang; Jun-Wei Yu; Yu-Ou Teng (Food Chemistry, 2026)

Green and efficient extraction of polyphenols from Lycium barbarum leaves using a betaine-based natural deep eutectic solvent: Process optimization, mechanistic elucidation, and bioactivity evaluation - Ya-Jie Yuan; Zhen Liu; Yu-Ru Wang; Jing-Yi Wang; Qian Ma; Cen Xiang; Jun-Wei Yu; Yu-Ou Teng (Food Chemistry, 2026)

Interventional mechanisms of antioxidants on flavor profile modification in the fermented egg white powder system - Ru-yi Zhang; Zhi-shuo Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2026)

Cissatriterpenoids D-L, nine undescribed polyhydroxylated oleanane triterpenoids from Cissampelos pareira var. hirsuta - Shuang-Qin Cao; Ru-Yi Pan; Tong-Tong Zhang; Jian-Hong Gong; Meng Li; Hui Chen; Jing-Ke Zhang; Zhi-You Hao; Xiao-Ke Zheng; Yan-Jun Sun; Wei-Sheng Feng (Phytochemistry, 2026)

Novel Lactobacillus Strains Alleviate E. coli-induced Inflammation in a Urinary Tract Infection Rat Model - Sini Kang; Zhihua Peng; Ru Wei; Jiaxin Liu; Hee-Jun Kim; Yongjun Lee; Moonjin Ra; Eun Ji Kim; Heo Keon; Jong Ik Jeon; Min Ji Jang; Myeong Soo Park; et al. (Probiotics and Antimicrobial Proteins, 2026)

Long-term intercropping increases soil aggregate stability by altering soil colloid content and stability - Chuan-Lin Xiao; Jing-Ru He; Cheng-Bao Wang; Wei-Ping Zhang; Jun Mao; Peter Christie; Jian-Ying Shang; Long Li (Plant and Soil, 2026)

Manganese acts as savior rather than accomplice of antibiotic stress: Dual cycles of ROS scavenging and Mnammox - Dong-Jun Hou; Wei-Lin Guo; Qian-Ru Liu; Hong-Wei Yang; Qiu-You Xu; Yun-Fei He; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Mechanism of adsorption and biodegradation of typical antibiotics by sediments in mariculture tailwater system - Jun-Ru Zhao; Xing Li; Yan-Ling Yang; Zhi-Wei Zhou; Ze-Dong Lu; Xiao-Yan Fan (Environmental Research, 2026)

Modulating limonin release via pectin fine structure in Ca2+-citrus pectin emulsion gels - Wei-yun Zhang; Jin-song Liao; Jun-ru Qi (Food Research International, 2026)

Behaviors and adaptive strategies of anammox microbiota in response to typical ionic liquid: Metabolic compensation and gene regulation - Dong-Jun Hou; Wei-Lin Guo; Hong-Wei Yang; Qian-Ru Liu; Nian-Si Fan; Ren-Cun Jin (Bioresource Technology, 2026)

Synthetic microalgae community promotes chili growth planted in waste stone powder by enriching beneficial root endophytic bacteria and fungi - Cong Liu; Hongqing Wei; Shaoguo Ru; Weizhong Wang; Zhengmao Li; Lijuan Liu; Xiukai Song; Jun Wang (Plant and Soil, 2026)

Overlooked Roles of Pharmaceutical Metabolic Products in Stimulating Microbial Metabolism and Antibiotic Resistance Gene Dissemination of Anaerobic Sludge - Jing Wu; Dan Sun; Yuan Pan; Dong‐Feng Liu; Hui Zhang; Jun‐Hua Zhou; Tong Gao; Jie Wu; Ru‐Li He; Yin‐Guang Chen; Wen‐Wei Li (Environmental Microbiology, 2026)
The roles of non‐antibiotic pharmaceuticals in shaping the dissemination behaviours of antibiotic resistance genes (ARGs) in wastewater treatment systems remain poorly understood, and the influences of their transformation products have been overlooked. Here, we unveil more profound impacts of the metformin (MET) biotransformation product than the parent pollutant on the microbial community structure and ARG propagation of wastewater anaerobic sludge. The exposure to MET and its metabolic products guanylurea (GUA) at environmentally relevant concentrations both raised the methane production and resulted in up to 52.5% higher sludge ARGs abundance relative to the unexposed control. Especially, the GUA group showed up to 188‐fold upregulation in several ARGs including bcrA , PmrF , acrB and mexF , enabled 3218‐fold enrichment of plasmids from several bacteria. The underlying mechanisms were elucidated by integrated metagenomics, molecular dynamics simulations, and metabolic profiling analyses. MET and GUA were found to trigger coordinated cellular responses including disrupted glycerophospholipid metabolism, increased membrane permeability and broad metabolic reprogramming, which collectively boosted the ARGs dissemination. Overall, this work establishes a mechanistic link between micropollutant‐induced microbial stress and ARGs propagation in anaerobic sludge, and advocates for re‐evaluating the environmental risks of non‐antibiotic pharmaceuticals and integrating resistance control into wastewater management framework.

A new norlignan and other compounds from Artemisia frigida Willd - Xin-Ya Dong; Ru-Ya Li; Hong-Xia Tang; Ya-Jie Li; Jun Chen; Jin-Guo Luo; Na Yu; Xiang-Wei Xu; Xu-Dong Zhou (Biochemical Systematics and Ecology, 2025)

GZR101, a Novel Premixed Insulin for the Treatment of Diabetes Mellitus - Wei Chen; Cheng Cui; Wancai Xing; Yining Zhang; Anshun He; Yue Wang; Yan Huang; Nannan Zhai; Qimin Shi; Fangkai Xue; Yongchun Wang; Jun Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Waste to wealth: High-internal phase Pickering emulsions stabilized by defatted flaxseed particles were employed as a novel animal fat replacer in meat systems - Cheng-wei Ruan; Si-ying Huang; Jun-ru Qi; Qingrong Huang (Food Chemistry, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Physicochemical and rheological properties of konjac glucomannan and its mixed gels with κ-carrageenan: Effect of deacetylation by L-arginine - Ting Zhuo; Jun-ru Qi; Jin-song Liao; Hui-ying Wei; Rong Xiao (Food Chemistry, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Explore the synergistic effects of Lactobacillus plantarum fermentation and tea polyphenols on the deodorization of egg white powder from the perspective of protein site competition - Ru-yi Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2025)

Citrus endogenous components as prebiotics: Advances in extraction, digestion, mechanisms, and delivery - Wei-yun Zhang; Jin-song Liao; Jun-ru Qi (Food Research International, 2025)

Modulation of gut microbiota by pectin: The critical role of degree of esterification and rhamnogalacturonan-I ratios - Wei-yun Zhang; Jin-song Liao; Jun-ru Qi (Food Bioscience, 2025)

Co-influence of the degree of esterification and degree of amidation on the properties of acid-sugar-calcium amidated pectin gels - Hui-ying Wei; Jun-ru Qi; Jin-song Liao; Ting Zhuo; Rong Xiao (Food Hydrocolloids, 2025)

Rhizobium inoculation improves yield advantages and soil Olsen phosphorus by enhancing interspecific facilitation in intercropping - Jun Mao; Ping Wang; Chuan-Lin Xiao; Jin-Pu Wu; Wei-Ping Zhang; Jing-Ru He; Hans Lambers; Long Li (Plant and Soil, 2025)

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Thiophene-containing conjugated polymers modified Zn0.5Cd0.5S inorganic/organic S-scheme heterojunction for boosting photocatalytic hydrogen production coupled with benzyl alcohol oxidation - Lele Wei; Ru Song; Jiarui Song; Yaping Li; Yina Nie; Lin Liu; Jun Wan (Chemical Engineering Journal, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Cysteine and glycine-rich protein 2 is crucial for maintaining the malignant phenotypes of gliomas through its action on Notch signalling cascade - Lingtong Liu; Fei Li; Lingxue Zhang; Yingying Cheng; Lin Wu; Ru Tie; Xiaobing Jiang; Wenwen Gao; Bochuan Liu; Yao Wei; Pan Chang; Jun Xu; et al. (Toxicology and Applied Pharmacology, 2024)

Uptake, translocation, and metabolism of organophosphate esters (OPEs) in plants and health perspective for human: A review - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yu-Fei Feng; Long-Wei Zhang; Xue-Yi Jiang; Yi-Shan Liu; Dong-Wei Wu; Jun-Jie Hu (Environmental Research, 2024)

Efficient removal of size-fractionated antibiotic resistance genes (ARGs) in WWTPs secondary effluent by vacuum ultraviolet (VUV) activated potassium peroxymonosulfate (PMS) - Xiao-Yan Fan; Shi-Long Xu; Xing Li; Zhi-Wei Zhou; Yu-Xi Gao; Jun-Ru Zhao; Zhong-Xing Zhang (Chemical Engineering Journal, 2024)

Time-dependent nonmonotonic concentration-response and synergism of alkyl glycosides with different alkyl side chain to Vibrio qinghaiensis sp. -Q67 - Meng-Ting Tao; Shu-Shen Liu; Ting-Ting Ding; Zhong-Wei Gu; Ru-Jun Cheng (Science of The Total Environment, 2024)

Inflammation and Brain Structure in Alzheimer’s Disease and Other Neurodegenerative Disorders: a Mendelian Randomization Study - Wei-Shi Liu; Ya-Ru Zhang; Yi-Jun Ge; Hui-Fu Wang; Wei Cheng; Jin-Tai Yu (Molecular Neurobiology, 2024)

Advances in the study of silica nanoparticles in lung diseases - Li-Hong Ao; Yun-Geng Wei; Hong-Ru Tian; Hua Zhao; Jun Li; Jia-Qi Ban (Science of The Total Environment, 2024)

Design, synthesis and insecticidal activity of benzenesulfonamide derivatives containing various alkynyl, alkenyl and cyclopropyl groups in para position - Jian-Jun Zhu; Tao Guo; Hong-Xiang Liu; Xin-Ru Tan; Zi-Wei Zhang; Wen-Jun Wu; Ji-Wen Zhang (Natural Product Research, 2024)

Study on low methoxyl pectin (LMP) with varied molecular structures cross-linked with calcium inducing differences in the gel properties - Chun-lin Wu; Jun-ru Qi; Jin-song Liao; Zi-wei Liu; Chun-ai He (Food Hydrocolloids, 2024)

Uptake mechanism, translocation, and transformation of organophosphate esters in water hyacinth (Eichhornia crassipes): A hydroponic study - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yi-Shan Liu; Long-Wei Zhang; Yu-Fei Feng; Xue-Yi Jiang; Dong-Wei Wu; Jun-Jie Hu; Guang-Guo Ying (Environmental Pollution, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Cyclodextrin-based metal-organic framework materials: Classifications, synthesis strategies and applications in variegated delivery systems - Ru-nan Zhao; Bei-wei Zhu; Yu Xu; Song-feng Yu; Wen-jun Wang; Dong-hong Liu; Jiang-ning Hu (Carbohydrate Polymers, 2023)

Accumulation degree and risk assessment of metals in street dust from a developing city in Central Taiwan - Tser-Sheng Lin; Jun-Wei Wu; Thi-Dieu-Hien Vo; Van-Truc Nguyen; Yun-Ru Ju (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Characteristics and driving factors of abandoned cultivated land in the hilly regions of southern China: A case study in Longnan, Jiangxi Province - Ze-bin Chen; Yong-lin Chen; Chao-jun Li; Jian-ping Lin; Pei-ru Chen; Wei-wei Sun; Zhi-wei Wan (Journal of Mountain Science, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Bisphenol S disrupts opsins gene expression and impairs the light-sensing function via antagonizing TH-TRβ signaling pathway in zebrafish larvae - Shuhui Wei; Liguo Qiu; Shaoguo Ru; Yang Yang; Jun Wang; Xiaona Zhang (Food and Chemical Toxicology, 2023)

Identifying the impact of Fe nanoparticles encapsulated by nitrogen-doped carbon to Fe single atom sites for boosting oxygen reduction reaction toward Zn-air batteries - Wen-Jun Niu; Ying-Yun Yan; Ru-Ji Li; Wei-Wei Zhao; Jiang-Lei Chen; Ming-Jin Liu; Bingni Gu; Wen-Wu Liu; Yu-Lun Chueh (Chemical Engineering Journal, 2023)

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Impacts of nanoplastics on life-history traits of marine rotifer (Brachionus plicatilis) are recovered after being transferred to clean seawater - Dong Wang; Shaoguo Ru; Wei Zhang; Zhenzhong Zhang; Yuejiao Li; Lingchao Zhao; Lianxu Li; Jun Wang (Environmental Science and Pollution Research, 2022)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Distribution and genetic variability of young-of-the-year greater amberjack (Seriola dumerili) in the East China Sea - Takamasa Hasegawa; Ching-Ping Lu; Sheng-Tai Hsiao; Tsubasa Uchino; Hsin-Ming Yeh; Wei-Chuan Chiang; June-Ru Chen; Chiyuki Sassa; Kazuyoshi Komeyama; Ryo Kawabe; Takashi Sakamoto; Satoshi Masumi; et al. (Environmental Biology of Fishes, 2020)
We examined the distribution and genetic variability of the greater amberjack Seriola dumerili in the East China Sea (ECS) from the mitochondrial DNA (mtDNA) control region of young-of-the-year (YOY) individuals, which may reflect the genetic characteristics of the spawning population. In the years 2016 and 2017, a total of 165 YOY S. dumerili were collected from two different locations in the ECS: the southern part of the ECS, and western Japanese coast. The spawning period was estimated using otolith daily increments from a total of 67 larvae and juveniles collected in the ECS. Results from size and age distribution indicated that S. dumerili spawned near the shelf break region in the southern ECS from January to April. Phylogenetic analysis based on mtDNA sequence data showed no significant genetic differentiation among samples collected from different locations, implying S. dumerili in the ECS is mainly composed of one population. S. dumerili around the Japanese coast may be originated from the southern ECS.

Enhanced Antitumor Efficacy of Curcumin-Loaded PLGA Nanoparticles Coated with Unique Fungal Hydrophobin - Lu Sun; Hui Xu; Jing-hua Xu; Shao-ning Wang; Jun-wei Wang; Hong-feng Zhang; Wei-ru Jia; Lin-sen Li (AAPS PharmSciTech, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

Contrasting Soil Bacterial and Fungal Communities between the Swamp and Upland in the Boreal Forest and their Biogeographic Distribution Patterns - Jing Li; Hang-Wei Hu; Zhang-Jie Cai; Yin-Ru Lei; Man-Yin Zhang; Wei Li; Jun-Tao Wang (Wetlands, 2019)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

Fast Marching and Runge–Kutta Based Method for Centreline Extraction of Right Coronary Artery in Human Patients - Hengfei Cui; Desheng Wang; Min Wan; Jun-Mei Zhang; Xiaodan Zhao; Ru San Tan; Weimin Huang; Wei Xiong; Yuping Duan; Jiayin Zhou; Tong Luo; Ghassan S. Kassab; et al. (Cardiovascular Engineering and Technology, 2016)

Functional expression of human serum albumin-tandem thrombopoietin mimetic peptide fusion protein as a novel thrombopoietin analog in Pichia pastoris - Meizhu Wang; Dejuan Zhi; Jun Xian; Yi Ru; Suzhen Wei; Na Wang; Yiyao Liu; Haiqing Wang; Yuejuan Pei; Meijuan Song; Yang Li; Hongyu Li (Biotechnology Letters, 2016)

Sodium Channel Voltage-Gated Beta 2 Plays a Vital Role in Brain Aging Associated with Synaptic Plasticity and Expression of COX5A and FGF-2 - Yan-Bin XiYang; You-Cui Wang; Ya Zhao; Jin Ru; Bing-Tuan Lu; Yue-Ning Zhang; Nai-Chao Wang; Wei-Yan Hu; Jia Liu; Jin-Wei Yang; Zhao-Jun Wang; Chun-Guang Hao; et al. (Molecular Neurobiology, 2016)

Differential effects of general anesthetics on anxiety-like behavior in formalin-induced pain: involvement of ERK activation in the anterior cingulate cortex - Cong Luo; Yan-Ling Zhang; Wei Luo; Fiona H Zhou; Chang-Qi Li; Jun-Mei Xu; Ru-Ping Dai (Psychopharmacology, 2015)

Identification of geranylgeranyl diphosphate synthase genes from Tripterygium wilfordii - Meng Zhang; Ping Su; Yong-Jin Zhou; Xiu-Juan Wang; Yu-Jun Zhao; Yu-Jia Liu; Yu-Ru Tong; Tian-Yuan Hu; Lu-Qi Huang; Wei Gao (Plant Cell Reports, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Comparative pharmacokinetics of oxytetracycline in blunt-snout bream (Megalobrama amblycephala) with single and multiple-dose oral administration - Ru-Qin Li; Yu-Wei Ren; Jing Li; Can Huang; Jun-hui Shao; Xiao-Xuan Chen; Zhi-Xin Wu (Fish Physiology and Biochemistry, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Non-pulmonary vein foci induced before and after pulmonary vein isolation in patients undergoing ablation therapy for paroxysmal atrial fibrillation: incidence and clinical outcome - Hui Cheng; Yin-yin Dai; Ru-hong Jiang; Qiang Liu; Ya-xun Sun; Jian-wei Lin; Zu-wen Zhang; Shi-quan Chen; Jun Zhu; Xia Sheng; Chen-yang Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

A novel deletion mutation of the ADAR1 gene in a Chinese patient with dyschromatosis symmetrica hereditaria - WEI-WEI LI; QIU-YUE WU; NA LI; DE-QUAN DENG; RU-SONG ZHANG; YING-XIA CUI; XIAO-JUN LI; XIN-YI XIA (Journal of Genetics, 2014)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

The prevalence of CD33 and MS4A6A variant in Chinese Han population with Alzheimer’s disease - Yu-Lei Deng; Li-Hua Liu; Ying Wang; Hui-Dong Tang; Ru-Jing Ren; Wei Xu; Jian-Fang Ma; Li-Ling Wang; Jun-Peng Zhuang; Gang Wang; Sheng-Di Chen (Human Genetics, 2012)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

MeJA-inducible expression of the heterologous JAZ2 promoter from Arabidopsis in Populus trichocarpa protoplasts - Yin Wang; Guan-Jun Liu; Xiu-Feng Yan; Zhi-Gang Wei; Zhi-Ru Xu (Journal of Plant Diseases and Protection, 2011)

Molecular characterization and expression analysis of elongation factors 1A and 2 from the Pacific white shrimp, Litopenaeus vannamei - Lei Wang; Yuan Liu; Wei-Na Wang; Wei-Jun Mai; Yu Xin; Jun Zhou; Wen-Yin He; An-Li Wang; Ru-Yong Sun (Molecular Biology Reports, 2011)